Discovery of multiple p-mode pulsation frequencies in the roAp star, HD 86181. Issue 4 (26th July 2021) - Shi, Fangfei; Kurtz, Donald W; Holdsworth, Daniel L; Saio, Hideyuki; Cunha, Margarida S; Zhang, Huawei; Fu, Jianning; Handler, G
ABSTRACT: We report the frequency analysis of a known roAp star, HD 86181 (TIC 469246567), with new inferences from Transiting Exoplanet Survey Satellite ( TESS ) data. We derive the rotation frequency to be νrot = 0.48753 ± 0.00001 d −1 . The pulsation frequency spectrum is rich, consisting of two doublets and one quintuplet, which we interpret to be oblique pulsation multiplets from consecutive, high-overtone dipole, quadrupole, and dipole modes. The central frequency of the quintuplet is 232.7701 d −1 (2.694 mHz). The phases of the sidelobes, the pulsation phase modulation, and a spherical harmonic decomposition all show that the quadrupole mode is distorted. Following the oblique pulsator model, we calculate the rotation inclination, i, and magnetic obliquity, β, of this star, which provide detailed information about the pulsation geometry. The i and β derived from the best fit of the pulsation amplitude and phase modulation to a theoretical model, including the magnetic field effect, slightly differ from those calculated for a pure quadrupole, indicating the contributions from ℓ = 4, 6, 8, ... are small. Non-adiabatic models with different envelope convection conditions and physics configurations were considered for this star. It is shown that models with envelope convection almost fully suppressed can explain the excitation at the observed pulsation frequencies.